Hora Libre, a television experience towards educommunication - Iovanna Caissón, Silvana Cristina (2019)
This article analyzes the experience of Hora Libre (Free Time), a television program hosted by boys, girls and young people on Argentine community TV channels between 2017 and 2018, as part of a series of public policies that promote exercising the right to communication. The topic will be approached from a critical perspective of educommunication, cultural studies, popular education theories and studies on communication policies in Argentina. In this way, a first systematization of the proposal will be carried out based on the analysis of the political-communication context, the intervening actors, the communication practices and the institutional logics which became evident in the project. Finally, this work is proposed as a space for reflection to act in future instances that bind the fields of communication and education in pursuit of strengthening democratic communication policies.